A low-cost wireless multinode vibration monitoring system for civil structures - Ribeiro, Renan Rocha (2023)
Structural health monitoring (SHM) has gained importance because many structures are approaching the end of their design life and demanding maintenance and monitoring. Low-cost solutions may push forward a widespread implementation of SHM on infrastructures but further investigation is still required to assess the performance of technically accessible, simple, and scalable low-cost systems. Tis work presents the development and validation of a low-cost vibration-based SHM multinode wireless system, based on the Arduino platform, for identifcation of modal parameters in civil infrastructures. Full details about the hardware and source code of the system are disclosed in an open repository, allowing its reproduction even by non-specialists in electronics. Te sampling frequency stability of the system is experimentally characterized, and interpolation postprocessing algorithms are proposed to solve inherent limitations. Te system is validated, and its performance is investigated in impulse and ambient vibration tests performed in a real-scale slab and a high-grade system. Te data obtained from the proposed system in impulse tests allowed estimation of natural frequencies within 2%, and MAC values around 0.3 to 0.9, in relation to those estimated with the high-grade system. However, the low-cost system was unable to produce usable data in ambient vibration tests.